LncRNA PAINT is associated with aggressive prostate cancer and dysregulation of cancer hallmark genes. Issue 4 (5th April 2021) - Hasan, Md Faqrul; Ganapathy, Kavya; Sun, Jiao; Khatib, Ayman; Andl, Thomas; Soulakova, Julia N.; Coppola, Domenico; Zhang, Wei; Chakrabarti, Ratna
Abstract: Long noncoding RNAs (lncRNAs) play regulatory role in cellular processes and their aberrant expression may drive cancer progression. Here we report the function of a lncRNA PAINT (prostate cancer associated intergenic noncoding transcript) in promoting prostate cancer (PCa) progression. Upregulation of PAINT was noted in advanced stage and metastatic PCa. Inhibition of PAINT decreased cell proliferation, S‐phase progression, increased expression of apoptotic markers, and improved sensitivity to docetaxel and Aurora kinase inhibitor VX‐680. Inhibition of PAINT decreased cell migration and reduced expression of Slug and Vimentin. Ectopic expression of PAINT suppressed E‐cadherin, increased S‐phase progression and cell migration. PAINT expression in PCa cells induced larger colony formation, increased tumor growth and higher expression of mesenchymal markers. Transcriptome analysis followed by qRT‐PCR validation showed differentially expressed genes involved in epithelial mesenchymal transition (EMT), apoptosis and drug resistance in PAINT ‐expressing cells. Our study establishes an oncogenic function of PAINT in PCa. Abstract : What's new? Long non‐coding RNAs have emerged as key regulatory molecules that are frequently aberrantly expressed in cancers. Here, the authors show that PAINT plays an oncogenic role in prostate cancer progression through modulation of the apoptosis, drug resistance, and epithelial‐mesenchymal transition gene networks. Furthermore, analysis of expression levels in patient tissues and transcriptome profiling of PAINT ‐expressing cells offer a global perspective on the involvement of PAINT in prostate cancer progression. The findings highlight the potential of PAINT to serve as a therapeutic target in treatment of aggressive prostate cancer.